The Implementation of Multistrategy Approach in Improving Arabic Language Skills at Medan Health Polytechnic Nursing - Kamalia, Kamalia (Institut Agama Islam Negeri Curup, 2024)
The research aimed to develop learning strategies that would meet the needs of nursing students through a multi-strategy approach. This study employed a quantitative method to measure the impact of the multi-strategy approach in learning Arabic at Medan Nursing Poltekkes. An experimental approach was utilized, with pre-test and post-test assessments administered to students using a questionnaire to test alternative hypotheses. Data from experiments and literature were analyzed using statistical tests such as T-Test. This study demonstrated that the multi-strategy approach led to a significant improvement in Arabic language skills among students at Medan Health Poltekkes, with the average skill level increasing to 96.85 from the previous 45.14. All students managed to reach the